Literature And Spirituality: The Implementation Of Islamic Values In Learning In The Era Of The Merdeka Curriculum - Parhan, Muhamad; Fadia, Rahma; Sofyan, Rhisma Al-Vyanie; Amelia, Rika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to explore and analyze the application of Islamic values in literature learning in the context of the Merdeka Curriculum. The main focus of the research is how Islamic values can be harmonized and applied in literary materials holistically, so as to build a deeper understanding for students. Using qualitative methods and interviews, this research identifies challenges and solutions in the implementation of Islamic values, particularly in relation to efforts to prevent controversy in its application. In addition, this research evaluates the impact of the implementation of Islamic values on learners' attitudes, both in terms of literary and religious understanding. The results of the study are expected to provide effective guidance for the implementation of Islamic value-based literature learning, while enriching the learner's literacy experience without causing conflict or significant differences in views. The implementation of Islamic values is expected to create uan inclusive, tolerant, and multicultural learning environment. Keywords: islamic values, literature learning, merdeka curriculum, multicultural education, controversy AbstrakPenelitian ini bertujuan untuk mengeksplorasi dan menganalisis penerapan nilai-nilai Islam dalam pembelajaran sastra pada konteks Kurikulum Merdeka. Fokus utama penelitian ini adalah bagaimana nilai- nilai Islam dapat diselaraskan dan diterapkan dalam materi sastra secara holistik, sehingga mampu membangun pemahaman yang lebih mendalam bagi peserta didik. Dengan menggunakan metode kualitatif dan wawancara, penelitian ini mengidentifikasi berbagai tantangan dan solusi dalam implementasi nilai-nilai Islam tersebut, khususnya terkait upaya untuk mencegah munculnya kontroversi dalam penerapannya. Selain itu, penelitian ini juga mengevaluasi dampak implementasi nilai-nilai Islam terhadap sikap peserta didik, baik dalam pemahaman sastra maupun agama. Hasil penelitian diharapkan dapat memberikan panduan yang efektif bagi penerapan pembelajaran sastra berbasis nilai keislaman, sekaligus memperkaya pengalaman literasi peserta didik tanpa menimbulkan konflik atau perbedaan pandangan yang signifikan. Implementasi nilai-nilai Islam diharapkan mampu menciptakan lingkungan belajar yang inklusif, toleran, dan multikultural. Kata Kunci: nilai-nilai islam, pembelajaran sastra, kurikulum merdeka, pendidikan multikultural, kontroversi